How Ground Penetrating Radar helps to understand the Nhecolândia lakes landscape in the Brazilian Pantanal wetland - Taioli, Fabio; Santos, Mauricio Guerreiro Martinho Dos; Assine, Mario Luis [UNESP]; Mendes, Deborah (Sociedade Brasileira de Geologia, 2021)
The Pantanal wetland is an active sedimentary basin representing a relevant depositional setting for alluvial sedimentation studies. However, sedimentation homogeneity and the lack of outcrops makes sedimentary analysis more difficult. The Lower Nhecolândia is located at the Southern edge of the Taquari river megafan, whose genetic origin has been disputed as fluvial or eolian deposition. GPR analysis was used to characterize the subsurface stratigraphy and understand the region’s geomorphic evolution. The 100 MHz GPR provided continuous good quality sections up to a depth of 8 m. Two continuous reflections are disconformities that bound three depositional sequences characterized by distinct radar facies. The lower facies presents an upper erosional truncation followed by reflections presenting ∼1.5 m deep channelized forms and concave-up low amplitude reflections. The intermediate facies (∼4 m thick) presents a base with erosional truncation followed by concave-upward forms, ∼10 m wide, 1–3 m deep, separated by 1–2 m, and offlapping geometry. The upper facies has a flat base and thickness of 2–4 m, with parallel reflections; it shows a strong correlation between the radar facies and the forms preserved in the landscape, suggesting that channelized fluvial streams did not form them. The results obtained indicate that GPR use in the Pantanal is an important method to elucidate its geologic evolution.
Keywords: Pantanal Basin; ground penetrating radar; Taquari megafan; radar facies; shallow stratigraphy